DIGITAL ECONOMY AS A FACTOR OF TRANSFORMATION OF ECONOMIC SYSTEMS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
In the field of production. Digital technologies are used to automate production processes, production management and product quality control. This leads to increased production efficiency, reduced costs and increased labor productivity. In the field of trade. Digital technologies are being used to develop online commerce, which allows consumers to access goods and services from anywhere in the world. This leads to expansion of sales markets and increased competition. In the service sector. Digital technologies are used to develop new types of services, such as online education, telemedicine, remote work and others. This leads to increased availability of services for the population.